METAPHORS WE SHOOT BY: METAPHORS IN LIVE TEXT FOOTBALL COMMENTARY - Atta-Asamoah, Obed (Universitas Islam Sumatera Utara (UISU), 2025)
This paper examines metaphors in live text football commentary, a developing genre of computer-mediated sports discourse. Drawing on Lakoff and Johnson’s CMT, live text commentaries of three final football matches were used as the data for the study. The commentaries included that of the 2025 UEFA Champions League, 2025 Conference League and 2025 Europa League. The commentaries were analysed using the Pragglejaz Group’s (2007) procedure for identifying metaphorically used words, enabling the study to systematically detect and classify lexical items whose contextual meanings diverged from their basic meanings. The results show that war, journey, construction and power domains were mapped onto various events in the football game. These domains functioned to frame football as a combative struggle (war), a contest for dominance (power), a structured and progressive movement toward a goal (journey), and a creative or strategic process (construction). The following conceptual metaphors were identified: A Football Match Is War, A Football Match Is Competition For Power, A Football Match Is A Journey and A Football Match Are Construction. The analysis provides support for the claim that metaphors are not merely stylistic choices but fundamental cognitive tools through which football discourse is structured and communicated.